Anomie, Social Alienation and Security in Armenian Society - Vartikyan, Aram (Journal of Sociology: Bulletin of Yerevan University, 2017)
The current era is distinguished by the unprecedented intensity of processes, changes, and developments, which partially condition the uncertainty, and social instability. The chaos of information flows, which is the source of permanent tensions, anxieties, fears deepens and brings about systematic continuity to them. The modern multidimensional man is the bearer of the many unpredictable risks resulting from the unstable, uncertain relations of the new century. In his turn, the modern RA citizen being the part of the above-mentioned processes is the bearer of the vulnerabilities and threats of the new system of values and norms, public relations, neo-liberal market economy, political management emerging parallelly with independence, as well as the ongoing Karabagh conflict. The mutilation of the institutional reproduction in the Armenian society, the deep social distrust and the large-scale individualization inherent to these conditions leave the citizens alone with their problems. As a result, only personal, limited strategies are formulated to resist, overcome and most importantly establish security, which deepens the social fragmentation, regulatory uncertainty, and instability. As a result, we lose the possibility to have a harmoniously collaborating social entity, which is of vital importance to the maintaining of the long-term security in Armenia
Keywords: security, social anomie, social alienation, social powerlessness, learned helplessness, social isolation